Geographical distribution of the Corona pandemic in Raperin District, Kurdistan Region of Iraq - Fatimah Qader Mustafa; Sakar Mohammed Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The Corona Virus (Covid19) pandemic is one of the most rapidly spreading pandemics in the world, and spatial analysis has shown, as well as the progress of means of transportation and mobility in the whole world, that had a great impact on the rapid spread of the epidemic, and that despite the state of panic that afflicts the whole world, the reality The situation indicates that the (Covid19) pandemic is not the first of its kind that swept the world after overcoming the stage of epidemics and famines due to its lack of continuity and the low death rate. The conditions of the geographical environment and ways of living related to food and cultural habits in China have been shown by time series analysis to identify the effect of time on the speed of the spread of the epidemic and predict its future that the pandemic continues to spread and increase unless something new occurs that changes the direction of its escalation as the discovery of a serum for treatment and that despite the state of panic that afflicts the whole world. This study is concerned with the geographical distribution of the pandemic, highlighting the relationship between the elements of natural and human geography, based on its negative effects on human life and on their living and economic conditions, and searching for methods of combating and preventing them.